MicroRNA-223-3p Protect Against Radiation-Induced Cardiac Toxicity by Alleviating Myocardial Oxidative Stress and Programmed Cell Death via Targeting the AMPK Pathway - Zhang, Dao-ming; Deng, Jun-jian; Wu, Yao-gui; Tang, Tian; Xiong, Lin; Zheng, Yong-fa; Xu, Xi-ming (Frontiers in Cell and Developmental Biology, 2022)
Objectives: Radiotherapy improves the survival rate of cancer patients, yet it also involves some inevitable complications. Radiation-induced heart disease (RIHD) is one of the most serious complications, especially the radiotherapy of thoracic tumors, which is characterized by cardiac oxidative stress disorder and programmed cell death. At present, there is no effective treatment strategy for RIHD, in addition, it cannot be reversed when it progress. This study aims to explore the role and potential mechanism of microRNA-223-3p (miR-223-3p) in RIHD. Methods: Mice were injected with miR-223-3p mimic, inhibitor or their respective controls in the tail vein, and received a single dose of 20 Gray Whole Heart Irradiation (WHI) for 16 weeks after 3 days to construct a RIHD mouse model. To inhibit adenosine monophosphate activated protein kinase (AMPK) or phosphodiesterase 4D (PDE4D), compound C (CompC) and AAV9-shPDE4D were used. Results: WHI treatment significantly inhibited the expression of miR-223-3p in the hearts, furthermore the levels of miR-223-3p decreased in a radiation time-dependent manner. miR-223-3p mimic significantly relieved, while miR-223-3p inhibitor aggravated apoptosis, oxidative damage and cardiac dysfunction in RIHD mice. In addition, we found that miR-223-3p mimic improves WHI-induced myocardial injury by activating AMPK, and that the inhibition of AMPK by CompC completely blocks these protective effects of miR-223-3p mimic. Further studies found that miR-223-3p lowers the protein levels of PDE4D, and inhibiting PDE4D by AAV9-shPDE4D block the WHI-induced myocardial injury mediated by miR-223-3p inhibitor. Conclusion: miR-223-3p ameliorates WHI-induced RIHD through anti-oxidant and anti- programmed cell death mechanisms via activating AMPK by PDE4D regulation. miR-223-3p mimic exhibits potential value in the treatment of RIHD.